9-(4-Methylphenoxycarbonyl)-10-methylacridinium trifluoromethanesulfonate - Trzybiński, Damian (International Union of Crystallography, 2010)
In the crystal structure of the title compound, C(22)H(18)NO(2) (+)·CF(3)SO(3) (−), adjacent cations are linked through C—H⋯π and π–π interactions, and the cations and anions are connected by C—H⋯O and C—F⋯π interactions. The acridine and benzene ring systems are oriented at a dihedral angle of 3.0 (1)°. The carboxyl group is twisted at an angle of 83.1 (1)° relative to the acridine skeleton. The mean planes of adjacent acridine units are parallel or inclined at an angle of 75.2 (1)° in the crystal structure.